Beef Storage Sanitation in a Five-Star Hotel from Chiller to Plate - IB Hariyanto, Oda; Wendy; Sihombing , Dame Afrina; Anggraini, Ratih (Politeknik Pariwisata Makassar, Indonesia, 2026)
The storage of beef in the main kitchen of a five-star hotel requires proper hygiene and sanitation procedures to maintain quality, particularly during major holiday periods. This study aims to identify how these procedures are implemented in beef storage as a key factor in guest satisfaction. The research uses a qualitative method with a case study approach at one five-star hotel. Data were obtained through observation, interviews, and documentation. The findings show that hygiene and sanitation practices among staff are generally well carried out. However, chiller cleanliness, storage temperature control, and beef arrangement are not fully in line with standard operating procedures. This study is limited to one hotel, so the findings cannot be generalized. Future research is recommended to involve more hotels, examine the duration of storage temperature application, and evaluate the effectiveness of hygiene and sanitation standard operating procedures.